(3cdjdI hOefIs - (3YHO Gddg Hf GdebaY , GHf GdebaY , CHh YeQ,J (B142 (3g` s
(3ChdgG (B:s
q (3GdZQHGf fgV aNdG Hg hGSJTGQg hSGdg Yf HOh YOGhI eG cGf Hjf GdZQHGf hGdHhe s
(3BNQgG (B:s
(3bGd GdLQOGfi bO CJjJc QGZHG WGdHG Edjc hbO jMb Ydjc EWdGdi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B140 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B156s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1507s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs